Pengaruh Model Pembelajaran Kooperatif Jigsaw Terhadap Hasil Belajar Pendidikan Agama Islam - Santika, Lia; Sulaiman, Sulaiman (Prodi Pendidikan Keagamaan Islam, 2023)
This research is motivated by teaching and learning process activities or learning activities. The learning process is still centered on the teacher which causes students to interact less and be less active during learning. This has an impact on the low learning outcomes of students. So it is necessary to apply various learning models that are in accordance with the material being taught so that students can be more active in participating in the learning process such as applying the jigsaw cooperative learning model. The purpose of this study was to determine the effect of applying the jigsaw cooperative learning model to the learning outcomes of PAI in class X at SMAN 1 Padang Gelugur. The research method used is a Quasi Experiment with a Post Test Only Control Group Design research design. The population in this study were all students in class X MIPA 1 – X MIPA 5 SMAN 1 Padang Gelugur for the 2022/2023 academic year consisting of 5 classes with a total of 180 people. Determination of the sample used in this study by purposive sampling technique so that class X MIPA 1 as the experimental class and X MIPA 2 as the control class with a total of 36 people in each class. The data obtained were analyzed using the prerequisite test, namely the normality test and homogeneity test, then a hypothesis test was carried out. The results of data analysis showed that there was a difference between the average experimental class learning outcomes with a value of 81.63 and the average control class with a value of 71.01. Based on the hypothesis test using the t test obtained T count (5.158) > T table (2.345) so that Ho is rejected and H1 is accepted. So it can be concluded that there is an influence of the jigsaw cooperative learning model on PAI learning outcomes in class X at SMAN 1 Padang Gelugur.